2019
DOI: 10.1158/1055-9965.epi-18-0240
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Translocation and Risk of Liver Cancer in a Finnish Cohort

Abstract: Background: Elevated systemic exposure to gut-derived bacterial products has been associated with hepatic inflammation and chronic liver diseases, potentially increasing the risk of liver cancer. However, only one prior study prospectively examined exposure to bacterial products in the circulation and risk of liver cancer, with a relatively limited coverage of biomarkers. Methods: We conducted a nested case-control study (224 liver cancer cases and 224 matched controls) in a large cohort of Finnish male smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…We further divided the LIHC cohort into high expression and low expression groups according to the median value of the LBP gene expression level and analyzed the differentially expressed genes between these two groups. Gene Ontology and KEGG analysis suggested that these genes clustered in acute-phase response and inflammatory response ( P < 0.01), which implied that LBP in live cancer cells may engage in the local immune response to gut-derived bacterial translocation, which was an etiological factor of HCC according to current reports ( 29 , 30 ). The association of LBP and clinicopathological parameters was further investigated by analyzing the LIHC cohort from TCGA.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We further divided the LIHC cohort into high expression and low expression groups according to the median value of the LBP gene expression level and analyzed the differentially expressed genes between these two groups. Gene Ontology and KEGG analysis suggested that these genes clustered in acute-phase response and inflammatory response ( P < 0.01), which implied that LBP in live cancer cells may engage in the local immune response to gut-derived bacterial translocation, which was an etiological factor of HCC according to current reports ( 29 , 30 ). The association of LBP and clinicopathological parameters was further investigated by analyzing the LIHC cohort from TCGA.…”
Section: Resultsmentioning
confidence: 85%
“…that LBP in live cancer cells may engage in the local immune response to gut-derived bacterial translocation, which was an etiological factor of HCC according to current reports (29,30). The association of LBP and clinicopathological parameters was further investigated by analyzing the LIHC cohort from TCGA.…”
Section: The Prognostic Significance Of Lbp Is Dependent On the Hepatmentioning
confidence: 99%
“…This acute inflammatory response turns to a chronic stage when the antigen-presenting cells become involved and present the antigens/microorganisms to immunocompetent cells expanding the antibody-secreting plasma cell population viral infection. [47][48][49][50] In 2007, our investigations in a murine model showed the promotion of DNA hypermethylation patterns in response to periodontal pathogen infection, where we found that The positive correlation between several inflammatory markers, epigenome, and gene expression, has been reported not only for US but also for other populations. 15,32,34,35 In a study evaluating methylation patterns in aggressive periodontitis cases, the DNA CpG methylation patterns of 22 inflammatory genes, collected from gingival biopsies taken from healthy patients and patients with aggressive periodontitis, showed higher methylation levels of CCL25 and interleukin-17C genes in healthy gingival tissue compared with periodontitis-affected tissue.…”
Section: Epigeneticmentioning
confidence: 62%
“…Recent progress in inflammation‐associated cancer research has unveiled the associations between chronic inflammatory conditions and carcinogenesis, through epidemiological data pointing to a correlation between the chronic inflammatory/infectious condition and a higher incidence of several types of cancer . There is also clear evidence showing specific microbial infection as a key contributing factor to the progress of various cancer types such as Helicobacter pylori ‐associated gastric cancer and hepatitis C virus‐positive liver carcinoma …”
Section: The Role Of Infection and Inflammatory Mediators In Cancer Dmentioning
confidence: 99%
See 1 more Smart Citation